CORRELATION OF LIPID PROFILE WITH INTERLEUKIN-12 IN TYPE 2 DIABETES MELLITUS - Meri Ponda Sari; Hanifah Maani; Ellyza Nasrul; Dia Rofinda (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Dyslipidemia is one of the common disorders in the diabetes mellitus (DM) patients causes cardiovascular disorders. Interleukin-12 (IL-12) is an important inflammation cytokine and elevated in type 2 DM (T2DM) which may contribute to inflammation of atherosclerotic plaque formation. Hyperglycemia, hyperlipidemia, hyperinsulinemia and oxidative stress that lead to endothelial dysfunction of atherosclerotic. The aim of this study to determine the correlation of lipid profile with IL-12 in T2DM. This study was an analytical study with cross-sectional design in 30 patients T2DM meet the inclusion and exclusion criteria and conduct blood tests at the Central Laboratory Installation of Dr. M. Djamil Hospital Padang in September 2016-August 2017. Level of lipid profile performed by the enzymatic colorimetric method. Sandwich ELISA used to measure the level of IL-12 in Biomedical Laboratory Medical Faculty of Andalas University. Spearman correlation was used, significant if p<0,05. The mean levels of total cholesterol, high-density lipoprotein, (HDL), triglycerides and low-density lipoprotein (LDL) in T2DM were 204.2 ± 42.8 mg/dL; 46.8 ± 9.3 mg/dL; 57 ± 53.4 mg/dL; 132.97 ± 41.0 mg/dL. The mean level of IL-12 in T2DM is 160.15 ± 99.05 pg/mL. Spearman correlation test of total cholesterol, (HDL), triglycerides and (LDL) with IL-12 are r= 0.228 (p=0.225); r= -0.234 (p=0.212); r= 0.415 (p=0.031); r= 0,215 (p=0.291) and analysis linear regression showed a moderate correlation between the levels triglycerides and Il-12 with r=0,512 and p<0,05. There is a moderate positive correlation between triglycerides, weak between total cholesterol and LDL with IL-12 and negative correlation between HDL with IL-12 in T2DM.